Pelaksanaan Program Penilaian Kepatuhan Penyelenggaraan Pelayanan Publik Terhadap Pemerintah Daerah Oleh Ombudsman Republik Indonesia Perwakilan Provinsi Bengkulu Tahun 2024 - Muhammad Rafif Arya Putra; Ricki Hasudungan Gultom; Derry Rahmat Saputra (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Public services are the first step for the public to receive or fulfill their needs from both government and private institutions. However, in the implementation of public services, maladministration practices are often found. The Ombudsman has a duty to prevent maladministration from occurring or recurring. One way is to conduct a public service compliance assessment program. This study uses a qualitative method with both primary and secondary sources through a descriptive approach. The purpose of this study is to examine the final score of the Bengkulu Provincial Government in implementing services and the benefits of this research to become a learning experience and improvement in the implementation of public services.